Community Currencies for a More Just and Equitable Society - Dama Madagow, Caroline (Interdisciplinary Journal of Partnership Studies, 2024)
To address systemic inequalities in our world, we need to re-imagine money, how it flows, and how it can be used as a tool for prosperity rather than a tool that deepens economic and social divides within communities. Most current monetary systems reward extractive tendencies, disassociating us from each other and from nature. These maladaptive systems alienate and suppress vulnerable communities, defining their value to society in reductive economic terms. Consequently, other inherent skills and resources that a community offers are overlooked. This article explores how community currencies, defined as local forms of exchange designed to support and strengthen local economies, can be tools for shared prosperity. It examines how these new social technologies have the potential to redesign how money flows in a more holistic and beneficial way.